Rani in the Mermaid Lagoon - Papademetriou, Lisa; Illustrated by he Disney Storybook Artists (London HarperCollins Children's Books, 2006)
Rani doesn't fit in. Without wings, she doesn't feel like she belongs with the other fairies. Rani sets off on a perilous journey to find a home, a journey that leads her underwater, deep into the lagoon, where the mermaids live.
Keywords: Mermaids -- Fairies -- Self-esteem